2017
DOI: 10.1016/j.addbeh.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Common and differential brain abnormalities in gambling disorder subtypes based on risk attitude

Abstract: Studying brain abnormalities in behavioral addiction including GD enables us to exclude possible confounding effects of exposure to neurotoxic substances, which should provide important insight that can lead to a better understanding of addiction per se. There have been a few brain structural magnetic resonance imaging studies for GD, although the results have been inconsistent. On the other hand, GD was suggested to be a heterogeneous disorder in terms of risk attitude. We aimed to examine the heterogeneity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…; Takeuchi et al . ). One principal component of the prospect theory is the probability weighting function.…”
Section: Introductionmentioning
confidence: 97%
“…; Takeuchi et al . ). One principal component of the prospect theory is the probability weighting function.…”
Section: Introductionmentioning
confidence: 97%
“…The behavior exhibited by such people is thought to be analogous to behavioral addiction, such as gambling or internet addiction. A recent neuroimaging study reported that gambling disorder patients showed reduced gray matter volume (GMV) in the left supramarginal gyrus and bilateral posterior cerebellum compared to healthy controls (Takeuchi, Tsurumi et al, ). Similarly, subjects with Internet addiction disorder showed GMV reduction in the anterior cingulate cortex, supplementary motor area, cerebellum, insula, and inferior temporal gyrus (Weinstein, Livny, & Weizman, for review).…”
Section: Introductionmentioning
confidence: 99%
“…The behavior exhibited by such people is thought to be analogous to behavioral addiction, such as gambling or internet addiction. A recent neuroimaging study reported that gambling disorder patients showed reduced gray matter volume (GMV) in the left supramarginal gyrus and bilateral posterior cerebellum compared to healthy controls (Takeuchi, Tsurumi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While a few studies have reported decreased OFC gray matter volume [13][14][15] and decreased cortical thickness 16 in pathological gamblers compared with healthy controls, other studies have failed to report significant group differences [17][18][19][20] . These inconsistencies might reflect the influence of factors such as age, comorbidities and head motion acting as confounds on structural brain measures 21 , as well as the heterogeneity existing among gamblers, as suggested by a recent study which found decreased OFC gray matter volume specifically in gamblers showing low risk-taking 22 . As a matter of fact, structural abnormalities observed in pathological gamblers are less consistent and of more modest magnitude than those reported in substance addiction 19,20,23 .…”
Section: Introductionmentioning
confidence: 99%